Assessing the Implementation of the Financial Assistance Program in Paracelis District Hospital, Mountain Province - Oredina, Miyako; Labasan, Glenn Paulo (International Journal of Sustainability and Advanced Integrated Research, 2026)
The Financial Assistance Program of Paracelis District Hospital plays an important role in helping patients manage medical expenses; however, limited information is available about its implementation and the challenges beneficiaries experience. This study assessed the program's implementation and identified the problems beneficiaries encountered in availing of its services. A quantitative descriptive-survey research design was employed involving 189 beneficiaries selected through stratified random sampling from a population of 346 inpatients and outpatients at Paracelis District Hospital, Mountain Province. Data were gathered using a researcher-made questionnaire that underwent expert validation and pilot testing, with a Cronbach’s Alpha reliability coefficient of 0.794. The data were analyzed using frequency counts, percentages, weighted mean, Mann-Whitney U Test, Kruskal-Wallis H Test, and Spearman’s Rho Correlation. The results showed that most respondents were female, unemployed, and outpatient beneficiaries. The implementation of the program was rated highly satisfactory, with respondents strongly agreeing that budget allocation, application procedures, and information dissemination were carried out effectively. Beneficiaries reported only minimal problems in accessing the program. Statistical analysis further revealed no significant differences in respondents’ assessments when grouped according to age, sex, employment status, and type of patient. Likewise, no significant relationship was found between the level of program implementation and the problems encountered by beneficiaries. The study concludes that the Financial Assistance Program is effectively implemented and significantly reduces patients' financial burden. The findings highlight the importance of sustaining effective program management while strengthening information dissemination, administrative processes, and monitoring mechanisms further to improve the accessibility and quality of financial assistance services.
Keywords: Financial Assistance Program, Budget allocation, Application process, Information dissemination, Paracelis District Hospital.